KAJIAN PENGGUNAAN KAPAL RO-RO SEBAGAI ALTERNATIF DALAM DISTRIBUSI LOGISTIK PADA KORIDOR JAKARTA – SURABAYA - M. Anjar Pamungkas (JOURNAL OF APPLIED SCIENCE (JAPPS), 2024)
The Pantura route is the main cross-corridor of the national economy that plays a major role in the national goods and services industry, most of the logistics delivery activities through this route use the road mode as one of the most choices. With limited road load and capacity, the Pantura route experiences many transportation problems that arise, from congestion, road damage due to overloading, increased road maintenance and maintenance costs and impacts on the environment, as well as other impacts that occur. Therefore, it is necessary to have other alternatives in organizing logistics in the Pantura corridor besides the road mode. The purpose of this study is to assess the potential of RO-RO as an alternative mode in the logistics of goods in the Pantura by comparing the cost structure between trucks and RO-RO modes, and formulating the RO-RO operating system for the Jakarta-Surabaya route or vice versa, by modeling the probability of switching modes using the Stated Preferences method. The variables used in this study are cost and travel time. By analyzing the reasons for choosing the mode used with the highest level of importance are cost and travel time. The conclusion of this study is that although the RO-RO fare is more expensive, but in general, the decrease in the level of road load and maintenance costs of the Pantura route can be transferred to the RO-RO operation plan